Metastable one-dimensional AgCl(1)-(x)I(x) solid-solution wurzite "tunnel" crystals formed within single-walled carbon nanotubes. - Sloan, J; Terrones, M; Nufer, S; Friedrichs, S; Bailey, SR; Woo, H; Rühle, M; Hutchison, J; Green, M (2002)
High-resolution transmission electron microscopy and spatially resolved electron loss spectroscopy have revealed that a eutectic mixture of AgCl and AgI crystallizes within single walled carbon nanotubes (SWNTs) as metastable AgCl(1-)(x)I(x) 1D solid solution crystals. The incorporated halide crystals form wurzite "tunnel" structures with locally varying Cl:I ratios and reduced Ag coordination.